2021
DOI: 10.1088/1361-6560/abc708
|View full text |Cite
|
Sign up to set email alerts
|

Specific absorbed fractions for a revised series of the UF/NCI pediatric reference phantoms: internal photon sources

Abstract: Assessment of radiation absorbed dose to internal organs of the body from the intake of radionuclides, or in the medical setting through the injection of radiopharmaceuticals, is generally performed based upon reference biokinetic models or patient imaging data, respectively. Biokinetic models estimate the time course of activity localized to source organs. The time-integration of these organ activity profiles are then scaled by the radionuclide S-value, which defines the absorbed dose to a target tissue per n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The advantage of our absorbed dose rate coefficients is that we can present them for males and females separately (table 4). However, these coefficients are primarily applicable to adults, and the elaboration of body-size-dependent absorbed dose rate coefficients that can be used for children and adolescents depends on future ICRP work on voxel phantoms for children (ICRP 2015, Schwarz et al 2021a, 2021b. We believe our organ dose coefficients readily can be used to calculate absorbed organ doses after protracted exposure both to occupationally exposed groups and members of the public after an accidental nuclear power plant release.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of our absorbed dose rate coefficients is that we can present them for males and females separately (table 4). However, these coefficients are primarily applicable to adults, and the elaboration of body-size-dependent absorbed dose rate coefficients that can be used for children and adolescents depends on future ICRP work on voxel phantoms for children (ICRP 2015, Schwarz et al 2021a, 2021b. We believe our organ dose coefficients readily can be used to calculate absorbed organ doses after protracted exposure both to occupationally exposed groups and members of the public after an accidental nuclear power plant release.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, each phantom was voxelized and post-processed using UF’s muscle and lymph node generator (Stepusin 2016; Schwarz et al 2021). Upon completion, the total body mass of each kneeling phantom was verified to be within 1.5% of the total body mass of the original standing series for consistency in the radiation transport simulations (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies by Schwarz et al (2021aSchwarz et al ( , 2021b, which employed the UF/NCI hybrid phantom series, demonstrated that organ distances play a significant role in the calculation of electron SAFs. Longer chord length distances that occur at greater pediatric ages have the effect of decreasing the estimated SAF (Schwarz et al 2021a).…”
Section: Review Of Prior Comparative Workmentioning
confidence: 99%
“…The RORNL series is hermaphroditic, in that one phantom contains the sex-specific organs of both the male and female anatomy. The UF/NCI series is a hybrid phantom series which has previously been converted into voxel format for use in Monte Carlo simulation tools (Lamart et al 2011, Dewji et al 2018, Khamwan et al 2018, Schwarz et al 2021a, 2021b. Figure 1 highlights the contrasting geometries of the two series (Schwarz et al 2011).…”
Section: Introductionmentioning
confidence: 99%